Curriculum Innovation in Assessment of Learning Outcomes through the Implementation of E-rapor - Ariyanti, Desi; Utanto, Yuli; Haryono, Haryono (Universitas Negeri Semarang, 2021)
This research aims to describe and analyze teachers' perceptions of the implementation of E-rapor policies as a form of reporting and documenting learning outcomes, implementation of E-rapor as part of curriculum innovation in aspects of learning outcomes, as well as supporting factors and inhibition of learning curriculum innovation through the implementation of E-rapor in schools. The type of research used is qualitative research case studies. Data retrieval uses interview techniques to dig deeper into the implementation of E-rapor; observations to observe the condition of the school, the level of competence of teachers in using IT, and the infrastructure facilities used in the implementation of E-rapor; and documentation studies to strengthen the data obtained from the interview results. Data validity checks are conducted with data triangulation and source triangulation to compare and re-examine the degree of trust in information obtained through in-depth interviews. Data analysis using qualitative descriptive models based on the stages of data collection, reduction, presentation, and verification. The results of this study show that: 1) The emergence of various positive and negative perceptions of teachers acting as E-rapor users on E-rapor implementation policies as part of curriculum innovation, 2) Implementation of E-rapor has been developed how to use in accessing E-rapor applications that can not only be accessed through intranet networks in schools but can also be done online at home in processing the learning results of students , 3) Supporting factors and inhibition of learning curriculum innovation through the implementation of E-rapor is fully realized as a determinant of success in its implementation. The implementation of E-rapor conducted online is part of curriculum innovation that plays a very important role in the assessment of students' learning outcomes in schools. With these innovations, documenting the reporting of student learning assessments can be implemented effectively and efficiently resulting in a more accurate, transparent, and accountable report.